An Analysis of Educational Values in Coach Carter Movie - Lelloltery, Marco Frank; Saleman Hartoyo; Marlina Kora (Indonesian Journal Publisher, 2025)
Education plays a crucial role in shaping behavior and actions in today’s rapidly advancing global era. With the emergence of sophisticated information technology, people can utilize various tools, including literature, to foster character development. Literature, encompassing poetic, dramatic, or fictional works, communicates human experiences and employs narrative techniques. Among its forms such as songs, short stories, novels, poems, and movies, this study focuses specifically on movies as a medium of education. Movies, a type of audio-visual communication, convey ideas through dialogue, action, and visuals. The Coach Carter movie is notable for its engaging narrative and educational value. This research aims to analyze the educational values embedded in the Coach Carter movie, using the KEMENDIKNAS framework. A qualitative descriptive method was employed, with data collected through repeated viewing of the movie, script transcription, and content analysis. Key steps included classifying educational values, analyzing frequently occurring themes, and drawing conclusions. The findings revealed five prominent educational values: discipline, responsibility, hard work, creativity, and love for peace. Specifically, the movie demonstrates these values with notable frequencies: discipline (D.1–D.11), responsibility (R.1–R.17), hard work (HW.1–HW.18), creativity (C.1–C.10), and love for peace (LP.1–LP.18). These values highlight the movie’s potential as a tool for educational enrichment, showcasing how narrative and character development within films can instill essential life skills and moral principles. This study underscores the role of movies in promoting education and their significance in character building.